Incremental value of magnetic resonance neurography of Lumbosacral plexus over non-contributory lumbar spine magnetic resonance imaging in radiculopathy: A prospective study - Chhabra, Avneesh (World J Radiol, 2016)
AIM: To test the incremental value of 3T magnetic resonance neurography (MRN) in a series of unilateral radiculopathy patients with non-contributory magnetic resonance imaging (MRI). METHODS: Ten subjects (3 men, 7 women; mean age 54 year and range 22-74 year) with unilateral lumbar radiculopathy and with previous non-contributory lumbar spine MRI underwent lumbosacral (LS) plexus MRN over a period of one year. Lumbar spine MRI performed as part of the MRN LS protocol as well as bilateral L4-S1 nerves, sciatic, femoral and lateral femoral cutaneous nerves were evaluated in each subject for neuropathy findings on both anatomic (nerve signal, course and caliber alterations) and diffusion tensor imaging (DTI) tensor maps (nerve signal and caliber alterations). Minimum fractional anisotropy (FA) and mean apparent diffusion coeffcient (ADC) of L4-S2 nerve roots, sciatic and femoral nerves were recorded. RESULTS: All anatomic studies and 80% of DTI imaging received a good-excellent imaging quality grading. In a blinded evaluation, all 10 examinations demonstrated neural and/or neuromuscular abnormality corresponding to the site of radiculopathy. A number of contributory neuropathy findings including double crush syndrome were observed. On DTI tensor maps, nerve signal and caliber alterations were more conspicuous. Although individual differences were observed among neuropathic appearing nerve (lower FA and increased ADC) as compared to its contralateral counterpart, there were no significant mean differences on statistical comparison of LS plexus nerves, femoral and sciatic nerves (P > 0.05). CONCLUSION: MRN of LS plexus is useful modality for the evaluation of patients with non-contributory MRI of lumbar spine as it can incrementally delineate the etiology and provide direct objective and non-invasive evidence of neuromuscular pathology.